Pengembangan Media Pembelajaran Matematika Deaf Logic Dalam Meningkatkan Kemampuan Operasi Hitung Penjumlahan Bilangan Pada Siswa Tunarungu - Amrina Rosada Z; Marlina Marlina (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2019)
The study was conducted based on the problems found in the reality. There are deaf students who have difficulty in solving the counting operations in mathematics learning due to a lack of innovation in the use of teaching aids or media on the learning process or learning. The purpose of this study is to validate and develop mathematics learning media logic in improving the ability to counting number operations in deaf students. The type of research used is research & development, which is a research method used to produce certain products and test the validity of these products. The subject of this research and development trial is by related experts such as mathematicians and children with special needs specifically.The result of the data from the experts' validation test on the mathematics deaf logic learning media in improving the ability to calculate the counting numbers of deaf students based on four aspects, that is practicality aspect, the usefulness aspect and the feasibility aspect. Then, the mathematics learning media from the logic is revised by being re-developed, so that it can obtain the specifications as it. The final form of this product is in the form of mathematical learning media logic in improving the ability to counting number operations in deaf students.